Pathology of Red Blood Cells in Patients with SARS-CoV-2 - Sona Hakobyan; Lina Hakobyan; Liana Abroyan; Aida Avetisyan; Hranush Avagyan; Nane Bayramyan; Lyudmila Niazyan; Mher Davidyants; Knarik Sargsyan; Tehmine Ghalechyan; Anna Semerjyan; Elena Karalova; et al. (Biomedicines)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has been associated with various hematological disorders. Understanding the pathology of erythrocytes (red blood cells) in coronavirus infection may provide insights into disease severity and progression. Objective: To review and analyze the general pathology of erythrocytes in patients infected with SARS-CoV-2, focusing on clinical and laboratory findings across different severity groups. Methods: Patients were classified into four groups based on clinical criteria: Group 1: Regular group (fever, respiratory symptoms, and radiographic evidence of pneumonia). Group 2: Severe group (shortness of breath >30 breaths/min, peripheral blood oxygen saturation <92% at rest, extensive pneumonia, respiratory failure requiring mechanical ventilation, and/or organ failure necessitating intensive care). Group 3: Low saturation group (peripheral blood oxygen saturation <85% at rest). Group 4: Erythroblastosis group (erythroblast count >0.5% among total nucleated blood cells). Clinical laboratory investigations included major routine studies and scanning microspectrophotometry to measure hemoglobin (Hb) spectra in unstained erythrocytes. Results: Erythroblasts were detected in approximately 30% of SARS-CoV-2 patients, predominantly in the severe group. Serum ferritin, C-reactive protein (CRP), and anisocytosis were strongly correlated with disease severity. Microspectrophotometric studies revealed significant changes in hemoglobin adsorption spectra, with an increase in Hb absorbance at 420 nm in severe cases compared to normal controls. Conclusions: Elevated serum ferritin, CRP levels, anisocytosis, and altered hemoglobin absorption at 420 nm wavelength are associated with adverse outcomes in SARS-CoV-2 infection. These findings highlight the potential utility of hematological parameters as markers for disease severity and prognosis in viral infections.